Risk markers for suicidality in autistic adults - Cassidy, Sarah; Bradley, Louise; Shaw, Rebecca; Baron-Cohen, Simon (BioMed Central, 2018)
Background: Research has shown high rates of suicidality in Autism Spectrum Conditions (ASC), but there is lack of research into why this is the case. Many common experiences of autistic adults, such as depression or unemployment, overlap with known risk markers for suicide in the general population. However, it is unknown whether there are risk markers unique to ASC that require new tailored suicide prevention strategies.